Haar wavelet characterization of dyadic lipschitz regularity - Arias, Carlos Exequiel (2022)
We obtain a necessary and sufficient condition on the Haar coefficients of a real function f defined on R+ for the Lipschitz α regularity of f with respect to the ultrametric δ(x, y) = inf{|I| : x, y ∈ I; I ∈ D}, where D is the family of all dyadic intervals in R+ and α is positive. Precisely, f ∈ Lipδ (α) if and only if D f, hj k E ≤ C2 −(α+ 1 2 )j , for some constant C, every j ∈ Z and every k = 0, 1, 2, . . . Here, as usual h j k (x) = 2j/2h(2jx − k) and h(x) = X[0,1/2)(x) − X[1/2,1)(x).